BRAF inhibitor resistance of melanoma cells triggers increased susceptibility to natural killer cell-mediated lysis. Issue 2 (9th September 2020) - Frazao, Alexandra; Rethacker, Louise; Jeudy, Géraldine; Colombo, Marina; Pasmant, Eric; Avril, Marie-Françoise; Toubert, Antoine; Moins-Teisserenc, Helene; Roelens, Marie; Dalac, Sophie; Maubec, Eve; Caignard, Anne
Abstract : Background: Targeted therapies and immunotherapies are first-line treatments for patients with advanced melanoma. Serine–threonine protein kinase B-RAF (BRAF) and mitogen-activated protein kinase (MEK) inhibition leads to a 70% response rate in patients with advanced melanoma with a BRAF V600E / K mutation. However, acquired resistance occurs in the majority of patients, leading to relapse. Immunotherapies that activate immune cytotoxic effectors induce long-lasting responses in 30% of patients. In that context, combination of targeted therapies with immunotherapy (IT) is a promising approach. We considered boosting natural killer (NK) cell tumor immunosurveillance, as melanoma cells express stress-induced molecules and activate NK cell lysis. Methods: Here we have generated vemurafenib (a BRAF inihibitor)-resistant (R) cells from BRAF V600E SK28 and M14-sensitive (S) melanoma cell lines and investigated how resistance interferes with immunogenicity to NK cells. We determined the levels of several soluble molecules including NK ligands in 61 melanoma patients at baseline and 6 months M post-treatment with targeted therapies or immunotherapies. Results: Vemurafenib resistance involved activation of p-AKT in SK28R and of p-MEK/p-ERK in M14R cells and was accompanied by modulation of NK ligands. Compared with S cells, SK28R displayed an increased expression of natural killer group 2 D (NKG2D) receptor ligands (major histocompatibility complex class (MHC) I chain-related protein A (MICA) and UL16-binding protein 2 (ULBP2)) whereas M14R exhibited decreased ULBP2 . SK28R and M14R cells induced higher NK degranulation and interferon gamma secretion and were more efficiently lysed by donor and patient NK cells. SK28R showed increased tumor necrosis factor-related apoptosis-inducing ligand receptor II (TRAIL-RII) expression and TRAIL-induced apoptosis, and TRAIL-induced apoptosis of M14R was decreased. Combined BRAF/MEK inhibitors abrogated the growth of SK28S, M14S, and M14R cells, while growth of SK28R was maintained. BRAF/MEK inhibition attenuated NK activity but R cell lines activated polyfunctional NK cells and were lysed with high efficiency. We investigated the relationship of soluble NK ligands and response to treatment in a series of melanoma patients. Soluble NKG2D ligands known to regulate the receptor function have been associated to cancer progression. Serum analysis of patients treated with target therapies or IT indicates that soluble forms of NK ligands (MICA, B7H6, programmed cell death ligand 1, and carcinoembryonic antigen cell adhesion molecule 1) may correlate with clinical response. Conclusion: These results support strategies combining targeted therapies and NK-based immunotherapies.